Blind study on the action of digitoxin on elderly women - Starr, Isaac; Luchi, Robert J. (The American heart journal, 1969)
In 11 elderly women, all in normal rhythm, and some with manifest heart disease, digitoxin and control periods, each of about a month's duration, were alternated. In 6 patients who had been taking digitoxin daily for many years, the drug was withdrawn. A few acute experiments were made. Both the patients and the observers were “blind”; the latter attempted to identify digitoxin action both by the ordinary clinical observations, and by records of the ULF force BCG and the carotid pulse derivative. The results were completely negative. Neither subjects nor observers could distinguish between the digitoxin and control periods. Statistical analysis disclosed no significant differences. Surprised by the negative results, the authors asked the Food and Drug Administration to test the digitoxin used; it met all official chemical and biological requirements, although it had failed to stimulate the frog heart in a type of test now discarded. In the great majority of our subjects, their hearts, though not stimulated by digitalis, were markedly stimulated by mild exercise. This demonstrates clearly: (1) that our failure to demonstrate digitoxin action in the majority cannot be attributed to incapacity of elderly hearts to respond to stimulation; (2) that the techniques used were fully capable of demonstrating cardiac stimulation when it occurred. That digitalis glycosides benefit some types of diseased hearts more than others has long been known and all types were not represented in our study. Our negative results do not indicate that such drugs should never be tried in elderly persons in normal rhythm; our studies detected no harm from digitoxin administration. Nevertheless, Mackenzie's skeptical view is strongly upheld by our negative results, and our findings contrast sharply with the therapeutic expectations of many doctors.